2009
DOI: 10.1111/j.1464-5491.2009.02703.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumorrhachis: a rare complication of diabetic ketoacidosis

Abstract: Pneumorrhachis: a rare complication of diabetic ketoacidosis FIGURE 2 Computerized tomography (CT) of the thorax confirming the presence of air in the soft tissues and pneumomediastinum and also revealing pneumorrhachis (air in the spinal canal).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…[17][18][19][20][21][22][23] The clear exception is pneumorachis in the polytrauma patient, in whom there is a significant chance of a spinal fracture. This results from breach of the integrity of the spinal canal, allowing air to seep or be forced into it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22][23] The clear exception is pneumorachis in the polytrauma patient, in whom there is a significant chance of a spinal fracture. This results from breach of the integrity of the spinal canal, allowing air to seep or be forced into it.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumorachis may be an indication of substantial vertebral column injury, especially when paraspinal hematoma, rib fractures, transverse process fractures, clavicle fractures, subcutaneous air, intramuscular air, pneumothorax, or hemothorax are also present. 18 Iatrogenic causes of pneumorachis are lumbar punctures, 19 incidental durotomy, 20 spine surgery, 21 lung resection, 22 and colorectal surgery. 9 Nontraumatic causes of pneumorachis include infection, 10,11 spontaneous pneumothorax, 12 barotrauma caused by acute asthma, 13 foreign body, 14 severe coughing, vomiting and Mü ller's maneuver, 15 open myelomeningocele in infants, 16 subarachnoid pleural fistula, 17 and diabetic ketoacidosis.…”
mentioning
confidence: 99%
“…All patients had DM: history of DM type 1 in 6 patients (3.4, 6, 10, 12, current report), DM of unspecified type-3, [ 7 , 8 , 11 ] and DM newly diagnosed on admission-2. [ 5 , 9 ] All patients had metabolic abnormalities “characteristic of DKA,” including 4 case reports not listing their initial laboratory values, [ 4 , 8 , 10 , 11 ] and 7 patients with listing of the following metabolic abnormalities that were highly characteristic of DKA (3, 5, 6, 7, 9, 12, current report): mean glucose level = 633 ± 152 (SD) mg/dL (range: 426–823 mg/dL, median = 667 mg/dL, N = 7); severely acidotic pH on arterial blood gas-5 [ 3 , 5 , 7 , 9 , 12 ] ; decreased serum sodium bicarbonate level due to metabolic acidosis-5 [ 3 , 5 , 6 , 7 , 12 ] or borderline low serum bicarbonate-1 (current report); excessive ketone bodies in blood-4, [ 3 , 5 , 7 , 9 ] or in urine-4 [ 5 , 6 , 9 , 12 ] ; high anion gap acidosis-2 [ 7 , 9 ] or severe base deficit-2 [ 6 , 12 ] ; and elevated beta hydroxybutyrate-1 (current report).…”
Section: Systematic Reviewmentioning
confidence: 92%
“…[ 3 ] Another rare cause is forceful vomiting in patients with diabetic ketoacidosis (DKA) which presumably causes pulmonary alveoli to rupture and alveolar air to escape and dissect through tissue planes to produce pneumomediastinum and epidural pneumatosis. This systematic literature review identifies 10 reported cases of this syndrome, [ 3 12 ] expanding the largest previous review of 6 cases [ 3 ] ; reports a new, eleventh (illustrative) case; and tentatively characterizes this syndrome as a novel pentad that facilitates syndrome evaluation, diagnosis, and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…a multidisciplinary setting. There is only one case report of a patient without underlying lung disease who needed a laminectomy for progressive neurological signs and symptoms for a massive PM and PR [17].…”
Section: Answermentioning
confidence: 99%